Will Europe Face A Lost Decade? A Comparison With Japan's Economic Crisis - Christoph A. Schaltegger; Martin Weder (Center for Research in Economics, Management and the Arts (CREMA), 2013)
After more than five years have passed since the start of the global financial crisis, many European countries are still suffering from financial instability, surging sover- eign debt, economic stagnation or decline, high unemploym ent and political turmoil. We compare consequences and policy measures during Europe's current crisis with those in Japan in the 1990s after the burst of a real estate and asset price bubble. We show that despite marked differences, there are many simila rities both in eco- nomic outcome and policy reactions. Given the complexity, severity and persistence of Europe's multiple crises, the threat of a Lost Decade similar to the one Japan has witnessed may not be unlikely. The paper concludes by presenting some of the les- sons learned from Japan and Europe.
Keywords: 330